العلاقة بين الدوافع للتعلم ومهارة الكلام لدى طلاب المعهد العصري - Wael Ali Al-Sayyid; Irfan Nur Alfil Lail (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to reveal the correlation between motivation and speaking skills. This research uses descriptive quantitative approach and correlation method using the Product Moment Correlation formula. The data was collected using observation and distributing questionnaires. The sample of this research is 30 students. After the researchers distributed a questionnaire, the results obtained were 3.7 (74) with the predicate "medium" while the muhadasah score obtained the result 73.3 with the predicate "good". The result of the correlation between motivation and muhadasah for students is 0.589. The table value at the 5% level is 0.373 and at the 1% level is 0.478. Therefore, the calculated value is greater than the table value, which means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected.